2012
DOI: 10.1080/00140139.2012.661085
|View full text |Cite
|
Sign up to set email alerts
|

Control-display mapping in brain–computer interfaces

Abstract: Incongruency in control-display mapping reduces task performance. In this study, brain responses, task and system performance are related to (in)congruent mapping of command options and the corresponding stimuli in a brain-computer interface (BCI). Directional congruency reduces task errors, increases available attentional resources, improves BCI performance and thus facilitates human-computer interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 68 publications
2
37
1
Order By: Relevance
“…An important question is which factors influence the multisensory effects. The available studies strongly suggest that congruency of multiple sensory stimuli is a very relevant factor to enhance emotional, cognitive, and behavioral effects (e.g., Baumgartner, Lutz, et al, 2006;Baumgartner, Valko, Esslen, & Jäncke, 2006;Belardinelli et al, 2004;Carles et al, 1999;Chen et al, 2011;Cottet et al, 2007;Doehrmann & Naumer, 2008;Driver & Noesselt, 2008;Gottfried & Dolan, 2004;Krishna et al, 2010;Mattila & Wirtz, 2001;O'Callaghan, 2012;Senkowski et al, 2008;Spangenberg et al, 2005;Thurlings et al, 2012). From an ecological perspective, multisensory congruency reduces stimulus uncertainty, which may explain why congruent (redundant) multisensory information is more quickly processed whereas incongruent (conflicting) multisensory information takes longer and elicits arousal (Gerdes et al, 2014).…”
Section: Are Effects Of Multisensory Stimuli Always Larger Than Thosementioning
confidence: 99%
See 1 more Smart Citation
“…An important question is which factors influence the multisensory effects. The available studies strongly suggest that congruency of multiple sensory stimuli is a very relevant factor to enhance emotional, cognitive, and behavioral effects (e.g., Baumgartner, Lutz, et al, 2006;Baumgartner, Valko, Esslen, & Jäncke, 2006;Belardinelli et al, 2004;Carles et al, 1999;Chen et al, 2011;Cottet et al, 2007;Doehrmann & Naumer, 2008;Driver & Noesselt, 2008;Gottfried & Dolan, 2004;Krishna et al, 2010;Mattila & Wirtz, 2001;O'Callaghan, 2012;Senkowski et al, 2008;Spangenberg et al, 2005;Thurlings et al, 2012). From an ecological perspective, multisensory congruency reduces stimulus uncertainty, which may explain why congruent (redundant) multisensory information is more quickly processed whereas incongruent (conflicting) multisensory information takes longer and elicits arousal (Gerdes et al, 2014).…”
Section: Are Effects Of Multisensory Stimuli Always Larger Than Thosementioning
confidence: 99%
“…As noted before, effects of sensory cues may be multiplied, disambiguated, vetoed, inhibited, or the stimulation may even lead to an emergent or novel effect (de Gelder & Bertelson, 2003;Gottfried & Dolan, 2004;Helbig & Ernst, 2008;Pourtois et al, 2005). Research shows that congruent and incongruent crossmodal conditions elicit different cortical activations (Belardinelli et al, 2004;Chen, Yeh, & Spence, 2011;Doehrmann & Naumer, 2008;Driver & Noesselt, 2008;Gottfried & Dolan, 2004;O'Callaghan, 2012;Senkowski, Schneider, Foxe, & Engel, 2008;Thurlings, van Erp, Brouwer, Blankertz, & Werkhoven, 2012). Congruent stimuli (temporal, spatial, or semantic/ associative) enhance activation in brain regions mediating stable object representations, whereas incongruent stimuli increase activation in regions involved in cognitive control (Watson et al, 2013).…”
Section: External Assessment Perspectivementioning
confidence: 99%
“…BCI performance of tactile ERP-BCIs (Brouwer et al, 2010; Thurlings et al, 2012a,b) is generally lower than that of gaze-dependent BCIs (Thurlings et al, 2012a,b). In addition, when a BCI is used as a control device in the context of a dual-task, for example to navigate in a game, BCI performance is even lower than in BCI-only tasks (Thurlings et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It claims that in comparison to an incompatible display-control pairing, a compatible pairing leads to higher effectiveness in the stage of mapping a display target to the corresponding response, and therefore more attentional resources are available for attending to the target. 14 Given the significance and importance of spatial compatibility, in the past 30 years, a great deal of work has been directed at understanding human information processing for different spatial relationships for stimulus and response arrays under different experimental and practical settings. 7,12,[14][15][16][17][18][19][20][21] In a recent experimental study, Chan and Chan 22 studied the SRC effect for a horizontal visual display with hand and foot controls ( Figure 1).…”
Section: Spatial Compatibilitymentioning
confidence: 99%
“…14 Given the significance and importance of spatial compatibility, in the past 30 years, a great deal of work has been directed at understanding human information processing for different spatial relationships for stimulus and response arrays under different experimental and practical settings. 7,12,[14][15][16][17][18][19][20][21] In a recent experimental study, Chan and Chan 22 studied the SRC effect for a horizontal visual display with hand and foot controls ( Figure 1). In their first experiment, with a two-dimensional (2D) front-rear and right-left signal layout and corresponding top-hand and downfoot controls, they found that it was advantageous to respond to the front signals with hand controls and the rear signals with foot controls.…”
Section: Spatial Compatibilitymentioning
confidence: 99%